A pilot study of sterile saline versus reverse osmosis water in traumatic laceration wound cleansing in Emergency Department in Hospital Universiti Sains Malaysia, Kelantan and Hospital Tengku Ampuan Afzan, Pahang - Hashim, Anas Amri (2015)
Introduction: Traumatic laceration wound is a common reason for people seeking treatment in emergency care setting. As for current practice, sterile saline is still the most common agent used in cleansing or irrigating the wound in the emergency department. In overseas, there have been studies on alternative cleansing agent particularly tap water, which have showed equal or better outcomes in term of wound infection. There is no previous study been conducted on wound cleansing using Reverse Osmosis water. Objectives: To compare the rate of wound infection between sterile saline and reverse osmosis water cleansing for traumatic laceration wound. Method: This study was a multicenter, prospective, randomised controlled trial conducted at two tertiary hospitals. Subjects were a convenience sample of adults presenting with acute simple traumatic laceration requiring wound cleansing. They were randomized using block randomization method to irrigation with ‘sterile saline’ or ‘reverse osmosis’ water. Wounds were closed in the standard fashion. Follow-ups were done on day 5 and 14 after the intervention to assess for outcome or wound infection Results: A total of 48 patients (n=48) were selected and randomised into RO water group (n=24) and Saline group (n=20) (4 patients withdrew). The infection rate for sterile saline cleansing was 5% (95% CI -4.55%, 14.55%) compared to RO cleansing which was 4.17% (95% CI -3.83%, 12.17%). Relative risk for RO water group was 0.834 (95%CI 0.056, 12.494) compare to saline group. Fisher’s Exact test showed no significant effect on type of cleansing agent on wound infection. Conclusion: There was no significant difference between reverse osmosis and saline on wound infection. Reverse osmosis water can be considered as alternative cleansing agent to sterile saline in acute uncomplicated traumatic laceration wounds.